Juvenile nasopharyngeal angiofibroma - M Manjunath; T A Deepak; K C Mayank (Wolters Kluwer Medknow Publications, 2011)
Juvenile nasopharyngeal angiofibroma (JNA) is a relatively uncommon neoplasm occurring almost exclusively in the nasopharynx of adolescent males) Occasional cases have extended to involve the oral cavity.' JNA is a histologically benign yet locally aggressive vascular head and neck tumor which affects almost exclusively adolescent boys. JNA is an uncommon tumor, with reported incidence between one in 5000 and one in 60.000 otolaryngology patients. It is estimated to account for only 0.05% of all head and neck neoplasms, but is nevertheless considered the most common benign neoplasm of the nasopharynx. The diagnosis of JNA is based on history, physical examination and radiographic studies. JNA has several characteristic radiographic features. A case of juvenile nasopharyngeal angiofibroma with intracranial involvement in a 15-year-old boy, its clinical and radiological presentations are reported in this article.